Penerapan Digital Marketing Dalam Menigkatkan Penjualan Produk Buket Bunga (Studi Kasus:Posie Florist) - Ailsacia Cyrilla Qaf; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2025)
Digital marketing is among the most successful and efficientmarketing models amidst the rapid and massive changes in technology. Compared to traditional advertising such as print or television ads, digital marketing is often more cost-efficient. The purpose of this study is to measure the effectiveness of online advertising in growing sales at Posie Florist, a business engaged in floristry. Through a participatory research approach, which actively involves itself in Posie Florist's digital marketing activities, including content development and social media management like the website, Instagram, and TikTok. Additionally, this study reveals a number of implementation problems digital marketing in SMEs, as well as finding that digital marketing contributes much to creating a pleasant brand image and increasing customer loyalty. Effective digital marketing strategies can also help Posie Florist reach a wider target market and compete in an increasingly competitive market. This study offers a significant involvement in thedevelopment of digital marketing science, especially in the context of SMEs, and provides practical recommendations for business actors who want to increase sales through digital channels.